2020
DOI: 10.1002/dvg.23366
|View full text |Cite
|
Sign up to set email alerts
|

Simple embryo injection of long single‐stranded donor templates with the CRISPR/Cas9 system leads to homology‐directed repair in Xenopus tropicalis and Xenopus laevis

Abstract: Summary We report model experiments in which simple microinjection of fertilized eggs has been used to effectively perform homology‐directed repair (HDR)‐mediated gene editing in the two Xenopus species used most frequently for research: X. tropicalis and X. laevis. We have used long single‐stranded DNAs having phosphorothioate modifications as donor templates for HDR at targeted genomic sites using the Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR‐associated protein 9 (CRISPR/Cas9) system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…In such cases, the procedures are briefly described by citing such protocols to avoid redundancy. In particular, this protocol is a detailed explanation of critical points from our published protocol (Nakayama et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the procedures are briefly described by citing such protocols to avoid redundancy. In particular, this protocol is a detailed explanation of critical points from our published protocol (Nakayama et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In advance, design a primer set for genomic PCR of CRISPR-treated embryos to amplify a 300-to 700-bp region containing the target site in the middle of this region (purple arrowheads in Fig. 1B) as described (e.g., Nakayama et al 2014Nakayama et al , 2020…”
mentioning
confidence: 99%
“…For example, a long single-stranded DNA template containing phosphothioate modifications has achieved mosaic correction of an existing X. tropicalis tyr pigmentation mutation in 35% of injected embryos. Similarly in X. laevis, the in-frame insertion of a fluorescent protein (sfGFP) fusion into the melanocyte-specific slc45a2 L-gene copy was also reported in 20% of the embryos [81]. Moreover, the Easi-CRISPR method in mouse zygote injections could install knock-in alleles with average efficiencies of 30-60% (see https://blog.addgene.org/easi-crispr-generating-knock-in-andconditional-mouse-models) [79,82].…”
Section: Dsb Repair Options For Larger Dna Sequence Insertions In Xenopus Embryosmentioning
confidence: 92%
“…Chief among these is the ability to easily inject reagents of choice into individual blastomeres at early stages, and, with the use of lineage tracing dyes and detailed fate maps, observe their direct and indirect effects throughout subsequent developmental stages (Figure 1b,e). Injectable reagents include plasmids and mRNA for overexpression experiments, morpholinos for knockdown of maternal or zygotic expression, and, recently, CRISPR/Cas9 for genome editing (Aslan, Tadjuidje, Zorn, & Cha, 2017; Bhattacharya, Marfo, Li, Lane, & Khokha, 2015; Blitz, Biesinger, Xie, & Cho, 2013; Guo et al, 2014; Naert et al, 2020; Naert & Vleminckx, 2018; Nakayama, Grainger, & Cha, 2020; Tandon, Frank, David Furlow, & Horb, 2017). Although all of these tools can be used in X. laevis or X. tropicalis , CRISPR approaches have more commonly been deployed in X. tropicalis due to its diploid genome, whereas the pseudotetraploid X. laevis is often preferred for overexpression experiments and for embryological, cell biological, and biochemical approaches because of its larger size (Harland & Grainger, 2011; Kakebeen & Wills, 2019a, 2019b).…”
Section: Drilling Down Into Mechanisms: Unique Opportunities Presentementioning
confidence: 99%
“…Recent improvements to both the X. laevis and X. tropicalis genomes have confirmed that the majority of human disorder risk genes are conserved in terms of sequence and syntenny in the frog (Hellsten et al, 2010; Mitros et al, 2019; Session et al, 2016). With this in mind, the optimization of CRISPR‐mediated genome editing in Xenopus (Aslan et al, 2017; Bhattacharya et al, 2015; Blitz et al, 2013; Guo et al, 2014; Naert et al, 2020; Naert & Vleminckx, 2018; Nakayama et al, 2020; Tandon et al, 2017) has allowed the targeted mutagenesis of disorder risk genes identified by patient sequencing efforts, with an ever‐growing list to investigate. Many of these experiments take advantage of the unilateral mutagenesis approach in F0 animals to allow the identification of subtle phenotypes by comparison to the contralateral control.…”
Section: Beyond Fundamentals: Modeling Disorders Of the Brain In Xenopusmentioning
confidence: 99%